A.) -2

B.) -1

C.) 1

D.) 2

E.) 3

**Solve the equation x² - x - 6 = -4, then substitute the value of x into (x + 2)(x - 3) + 5.**

x² - x - 6 = -4

x² - x - 2 = 0 {added 4 to each side}

(x - 2)(x + 1) = 0 {factored into two binomials}

x - 2 = 0 or x + 1 = 0 {set each factor equal to 0}

x = 2 or x = -1 {added 2 and subtracted 1 from each side}

**If x = 2:**(x + 2)(x - 3) + 5 {given expression}

= (2 + 2)(2 - 3) + 5 {substituted 2 for x}

= 4(-1) + 5 {added inside parentheses}

= -4 + 5 {multiplied}

= 1 {added}

**If x = -1:**(x + 2)(x - 3) + 5 {given expression}

= (-1 + 2)(-1 - 3) = 5 {substituted -1 for x}

= 1(-4) + 5 {added inside parentheses}

= -4 + 5 {multiplied}

= 1 {added}

**C.) 1**

**- Algebra House**